An inter‐laboratory evaluation of OD‐3 zircon for use as a secondary U–Pb dating standard. (28th August 2013) - Iwano, Hideki; Orihashi, Yuji; Hirata, Takafumi; Ogasawara, Masatsugu; Danhara, Tohru; Horie, Kenji; Hasebe, Noriko; Sueoka, Shigeru; Tamura, Akihiro; Hayasaka, Yasutaka; Katsube, Aya; Ito, Hisatoshi; et al.
Abstract Zircon OD‐3 from the Paleogene Kawamoto Granodiorite (Mihara body) in Japan has been identified as a potential multi‐grain secondary standard for U–Pb dating. We have carried out an inter‐laboratory evaluation in order to evaluate possible heterogeneity amongst the OD‐3 zircon grains. U–Pb ages were obtained using two analytical techniques (a sensitive high‐resolution ion microprobe and a laser ablation–inductively coupled plasma–mass spectrometry) in eight laboratories. All the 238U–206Pb ages show good agreement, with an overall weighted average 238U–206Pb age of 33.0 ± 0.1 Ma (2σ). The U–Pb age results revealed no significant variation or heterogeneity in the U–Pb ages of the OD‐3 grains. Twelve fission‐track (FT) ages from three laboratories are also reported, and have a weighted average of 32.6 ± 0.6 Ma (2σ). Despite the different closure and annealing temperatures of the U–Pb and FT chronometers, respectively, the FT age is in good agreement with the U–Pb age. This suggests that the OD‐3 zircon had a relatively fast cooling history and has not experienced later thermal annealing. The chronological dataset reported here clearly demonstrates that the OD‐3 zircon could be a useful and reliable secondary standard for use during U–Pb dating studies of Cenozoic zircons.